World Finance-Economic Crisis: The View to the Problems, Contradictions and Perspectives of the Settlemen - M A Ignatskaya; N A Kulikovskaya; G A Kulikovskaya (RUDN Journal of Economics, 2011)
Any other modern crisis, that has the global character, becomes exactly at the finance sphere, at the same time this sphere is the most controlled from the national level to the over national regulation mechanisms (the level of IMF). Thus there are the questions about the quality of such regulation and the perspectives of creation of new set of tools and mechanisms of regulation including over national level.